Antibody reactivity to Afmp1p antigen in penguins with probable and confirmed aspergillosis - Callico, Adriana; Thurber, Mary Irene; Bronson, Ellen; Barnes, Julie; Burgdorf-Moisuk, Anne; Buscaglia, Nicholas A.; Davis, Michelle; Duncan, Ann; Eustace, Ronan; Gyimesi, Zoltan S.; Hyatt, Michael W.; Neumann, Sara; et al. (Frontiers in Veterinary Science, 2025)
Penguins under managed care are widely considered to have high susceptibility to infection by Aspergillus spp. Antemortem laboratory diagnostic options vary in sensitivity and specificity, and antibody detection has been problematic in penguin species given elevated levels of reactivity observed in clinically normal patients using traditional whole antigen enzyme-linked immunosorbent assays (ELISA). In the present study, an alternative assay was implemented to detect reactivity to Afmp1p, an Aspergillus cell wall antigen, in samples obtained from several different penguin species. With confirmed infection, abnormal protein electrophoretograms were consistently observed, and gliotoxin was detected in the majority of cases. An increase in reactivity to Afmp1p was observed in penguins with confirmed (n = 18, p < 0.0001) and probable (n = 13, p = 0.08) aspergillosis versus normal adult penguins (n = 33). Interestingly, increased reactivity to Afmp1p (p < 0.0001) was noted in normal adult penguins (n = 33) versus juvenile penguins (n = 22, p < 0.0001). Overall, the area under the curve for this assay was 0.890, with a sensitivity of 94.4% and a specificity of 57.6%, with an antibody assay cutoff of 1.0. Increasing reactivity resulted in an increase in specificity. These data support the use of Afmp1p antibody quantitation as part of a diagnostic workup in penguins with suspected aspergillosis.